First molecular detection of Spiroplasma spp. in ticks from horses in Brazil - da Silva, Nathalia Xavier; Dias, Thomas Salles; Vignoli, Julia Alves; Dos Santos Machado, Leandro; Telleria, Erich Loza; de Almeida Pereira, Virginia Léo; do Nascimento, Elmiro Rosendo; da Cunha, Nathalie Costa (Ticks and tick-borne diseases, 2022)
The class Mollicutes comprises microorganisms that lack a cell wall, highly dependent on their host to survive. Within Mollicutes, the genus Spiroplasma comprises motile helical microorganisms associated with various insects and other arthropods. This study aimed to detect and characterize Mollicutes microorganisms in ticks of different species of veterinary importance, using molecular techniques. These ticks were collected from dogs, cats, cattle, and horses from Rio de Janeiro's metropolitan regions. They were morphologically classified and pooled according to their species for subsequent DNA extraction. These samples were tested by PCR using class Mollicutes-specific primers (16S rRNA) and positive amplicons were sequenced. The obtained DNA sequences were compared with other Mollicutes sequences deposited in GenBank. We found that four out of 745 (0.54%) of the tick pools were positive for members of the class Mollicutes, identified as Spiroplasma spp.; of the positive pools, one comprised Amblyomma sculptum adults and three comprised Dermacentor nitens nymphs. The present study describes Spiroplasma spp. in ticks in Brazil for the first time. Nevertheless, due to few reports on these microorganisms, further studies on epidemiology, virulence, and pathogenicity are needed.
Keywords: Brazílie; Animals; Horses; koně; RNA, Ribosomal, 16S; Nymph; Spiroplasma; klíšťata; zvířata; Ticks; RNA ribozomální 16S; Brazil; nymfa